МОНГОЛ УЛСЫН ГАЗАР ЗҮЙН БАЙРЛАЛ ТҮҮНИЙ ГЕОПОЛИТИКИЙН ОНЦЛОГ - Ц.Ганболд; Б.Гантулга (Politology, 2023)
Academically, the study of geopolitics involves the analysis of geography, history and social science with reference to spatial politics and patterns at various scales (ranging from the level of the state to international). Sir Halford Mackinder’s Heartland concept showing the situation of the "pivot area" established in the Theory of the Heartland.